KAJIAN TEKNIS DAN EKONOMIS PEMANFAATAN KAYU PERUPUK - I M Sulastiningsih; Setiasih Irawanti; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1996)
Formerly perupuk wood was not recognized as good raw material by wood working manufacturers. Because of the increasing scarcity of ramin wood, the perupuk   wood had gained the benefit of the situation as indicated by increasing demand and price of perupuk   wood.The technical and economic studies on perupuk   wood (Lophopetalum.   spp)  utilization  wascarried out at one wood working mill in Gresik, East Java in 1994.   The objectives of the study were to identify   kind  of products  resulted from perupuk    utilization,  recovery level of each product, productivity and efficiency ofperupuk wood working machineries,  and its value added.The study showed that kind of products  resulted from perupuk    utilization were moulding,smooth-four-side (S4S), finger jointed  stick, solid jointed  board and finger jointed  board. The average  recovery  of perupuk    utilization  was  55%  and  the highest  recovery  (65.60%) was obtained by smooth-four-side product.  The double planer machine had the highest productivity because all products  used the machine to get the standard dimensions. The efficiency of some perupuk    wood  working  machineries  still  low.   The  value  added  of perupuk    wood  working products  were 90%,  55%,   52%,  37% and  24% for  smooth-four-side,  finger jointed  board, moulding,  solid jointed board and fingerjointed stick respectively.Key words :   perupuk,   wood working,  recovery and value  added.